Relaxation technique to reduce stress for a caregiver of a mental illness patient - Arum Pratiwi; Rita Tri Subekti; Budi Kristanto; Abi Muhlisin (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Mental disorders require a long treatment which has an impact on the family's physical and psychological burden. Psychoeducation in the family becomes crucial to reduce stress on caregivers. Limited case studies still focus on providing therapy to families of mentally ill patients. This case reports aims to provide an overview and discourse on colleagues about how stress management is given to families with parents with mental disorders. Case presentation: A 32-year-old woman cares a mother with Schizophrenia. The woman was a main care provider in the family that complaint was anxiety at the thought of her mother suffering from a severe mental illness. Symptoms that appear in these women are sleep disturbances, headaches for a while, and difficulty concentrating. Examination of vital signs revealed normal pulse, blood pressure and body temperature. Stress management applied to these women is to provide progressive muscle relaxation therapy. The training was carried out at the family home for two activities, then the family was asked to do independent for one month. The achievement of stress management was measured using the Parenting Stress Scale between before and after relaxation exercises. There is a difference scores between before and after training from 81 to 72 but not significant. This is probably due to unresolved social support, one of which is stigma from neighbors. Conclusions: Relaxation technique procedures for severe mental illness caregivers have been successfully applied and have an effect on reducing stress levels, but there is no significant difference.Abstrak: Latar Belakang: Gangguan jiwa memerlukan penanganan yang lama yang berdampak pada beban fisik dan psikis keluarga. Psikoedukasi dalam keluarga menjadi sangat penting untuk mengurangi stres pada pengasuh. Studi kasus yang berfokus pada pemberian terapi kepada keluarga pasien gangguan jiwa masih terbatas. Laporan kasus ini bertujuan untuk memberikan gambaran dan wacana kepada sejawat tentang bagaimana manajemen stres diberikan pada keluarga dengan orang tua dengan gangguan jiwa. Presentasi kasus: Seorang wanita berusia 32 tahun merawat seorang ibu dengan Skizofrenia. Wanita tersebut adalah pemberi perawatan utama dalam keluarga yang mengeluhkan kecemasan karena memikirkan ibunya menderita gangguan jiwa kronis. Gejala yang muncul pada wanita tersebut adalah gangguan tidur, sakit kepala sesaat, dan sulit berkonsentrasi. Pemeriksaan tanda-tanda vital menunjukkan denyut nadi, tekanan darah dan suhu tubuh normal. Manajemen stres yang diterapkan pada wanita tersebut adalah dengan memberikan terapi relaksasi otot progresif. Pelatihan dilakukan di rumah keluarga selama dua kali, kemudian keluarga diminta untuk berlatih mandiri selama satu bulan. Pencapaian manajemen stres diukur dengan menggunakan Parenting Stress Scale antara sebelum dan sesudah latihan relaksasi. Ada perbedaan skor antara sebelum dan sesudah pelatihan dari 81 menjadi 72 tetapi tidak signifikan. Hal ini kemungkinan karena dukungan sosial yang belum terselesaikan, salah satunya adalah stigma dari tetangga. Kesimpulan: Prosedur teknik relaksasi pada caregiver gangguan jiwa berat telah berhasil diterapkan dan berpengaruh dalam menurunkan tingkat stres, namun tidak terdapat perbedaan yang signifikan.